PENGARUH STIMULASI HUMOR AUDIO VISUAL TERHADAP BURNOUT STUDY - Rahmawati -; Bangun Yoga Wibowo; Meilla Dwi Nurmala (Jurnal Penelitian Bimbingan dan Konseling, 2017)
Difficulties in learning (learning disability) causes a person can not learn the provision properly. The situation is maintained with the obstacles to the achievement of success. The purpose of this research is to develop contemporary counseling techniques of audio visual humor stimulation as an effort to overcome burnout study. The research method used is pilot test group post test post test control.. Measuring tool is student of FKIP Untirta number 139 is taken by purposive sample, with age 18-21 years and limitation of intelligence above average low - average. From 139 trayout groups, 13 experimental groups and 15 controls were obtained. In the experimental group the results of t test pretest and post test t arithmetic 19.324 and signs (2-tailed <0.05) 0.000 keyword difference of MBI pre test and post test. While in the control group, the result of pre test and post test t test 1,840 and sign (2-tailed> 0,05) 0,087 no difference in MBI pre test and post test.Keyword: learning disability, burnout, humor stimulation